Mapping the glycosyltransferase fold landscape using interpretable deep learning - Rahil Taujale (Nature Portfolio, 2021)
Glycosyltransferases (GT) are proteins that display extensive sequence and functional variation on a subset of 3D folds. Here, the authors use interpretable deep learning to predict 3D folds from sequence without the need for sequence alignment, which also enables the prediction of GTs with new folds.